Ações antropogênicas e implicações geomorfológicas na bacia do Ribeirão das Lajes (Buritizeiro-MG): enfoque na dinâmica de veredas - Santos Júnior, Antonio das Graças José dos (2023)
The Ribeirão das Lajes basin is located in the municipality of Buritizeiro, in the northern region of Minas Gerais, in an area known as Sertão das Gerais, with the strong presence of chapadas and veredas. Starting in the 1970s, agricultural projects were developed in the region, which were consolidated from the 1980s on, with extensive occupation of eucalyptus and pastures. These anthropogenic actions resulted in environmental implications related to morphogenetic processes and impacts on veredas. Thus, the objective of the work was related to investigate the history of interference promoted, as well as the consequences derived from anthropogenic actions reflected in geomorphological features of the Ribeirão das Lajes basin. For this it was proposed an anthropogeomorphological investigation applied from the retrospective geomorphological cartography, being organized geomorphological and natural cover mappings and land use, rescuing three scenarios: 1964, 1992 and 2021. It was found that the conditions of the physical environment (geological, geomorphological and pedological) denote susceptibility to morphodynamic processes. However, anthropogenic interference has also propitiated the dynamization of these processes in the Basin, causing the sedimentation and loss of vereda areas, especially in the upper basin, with intense occupation by eucalyptus and pastures, and more recently with irrigated grain and coffee agriculture. The history of interference promoted and the geomorphological consequences derived for the Ribeirão das Lajes Headwater Lagoon, the Vereda do Galhão, and the Vereda São Roque stand out. Still, from the point of view of the geomorphological evolution of the Basin, the recognition of the compartments is noteworthy: Tabular Plateau, Erosive Escarpment, Residual Plateaus, São Francisco Depression and Plains and Terraces of the São Francisco River. Finally, it is considered that the work brought important results derived from the application of retrospective geomorphological cartography to a rural environment, emphasizing the dynamics of veredas.